2016
DOI: 10.1186/s40249-016-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in and lessons learned during the implementation of the 1-3-7 malaria surveillance and response strategy in China: a qualitative study

Abstract: BackgroundChina has made great progress in malaria control over the last century and now aims to eliminate malaria by 2020. In 2012, the country launched its 1-3-7 surveillance and response strategy for malaria elimination. The strategy involves to case reporting within 1 day, case investigation within 3 days, and focus investigation and public health actions within 7 days. The aim of this study was to evaluate the challenges in and lessons learned during the implementation of the 1-3-7 strategy in China so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…During implementation of the 1-3-7 malaria surveillance strategy in China (which likewise requires case reporting within 1 day), the reporting of unconfirmed malaria cases was not considered problematic as long as the notification triggered further investigations including laboratory confirmation by day 3. 17 Ensuring universal availability of diagnostic confirmation, promoting the use of diagnostic tests at all levels, and providing the option to request for a reconfirmation of a case, for example, by a DMSO, could contribute to narrowing the identified gap. In a setting with microscopy capacity, a sample collected on a slide can be diagnosed on return of a temporarily absent microscopist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During implementation of the 1-3-7 malaria surveillance strategy in China (which likewise requires case reporting within 1 day), the reporting of unconfirmed malaria cases was not considered problematic as long as the notification triggered further investigations including laboratory confirmation by day 3. 17 Ensuring universal availability of diagnostic confirmation, promoting the use of diagnostic tests at all levels, and providing the option to request for a reconfirmation of a case, for example, by a DMSO, could contribute to narrowing the identified gap. In a setting with microscopy capacity, a sample collected on a slide can be diagnosed on return of a temporarily absent microscopist.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of China's 1-3-7 malaria surveillance, a qualitative study suggested that better transport, calling and making appointments in advance of investigations to avoid absences, and an increase in community acceptance may improve timeliness. 17 In Zanzibar, a replacement of the currently required in-person review of each case at the notifying HF, for example, with a smart phone-based interface allowing the transmission of individual patient details, may likewise improve timeliness. Inperson visits to all HFs, including those not notifying any cases, on a scheduled basis rather than for each notified case, might improve notification completeness and timeliness.…”
Section: Operational Coverage Of Reactive Case Detection In Zanzibarmentioning
confidence: 99%
“…4 President's Malaria Initiative/Centers for Disease Control and Prevention, Atlanta, Georgia, USA. 5…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…1). The 1-3-7 strategy was initially developed and implemented in China in 2012 [5][6][7] and has since been adapted to the local contexts in several country settings in Southern Africa and Southeast Asia [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Following the implementation of this 1-3-7 model, local malaria transmission was interrupted effectively in most parts of China, which accelerated the malaria elimination process [20,21,36]. Based on this success, the 1-3-7 model was recommended by WHO as an example for malaria surveillance model at elimination stage, in "Strategy for malaria elimination in the Greater Mekong Subregion: 2015-2030" and "Malaria surveillance, monitoring & evaluation: a reference manual" [37,38].…”
Section: Successful Implementationmentioning
confidence: 99%